FERDINAND DE SAUSSURE : GENESIS Y EVOLUCION DE SU PENSAMIENTO EN EL MARCO DE LA LINGUISTICA OCCIDENTAL. CONTRIBUCION A LA HISTORIA Y A LA TEORIA DE LA LINGUISTICA - Koerner, Konrad (BIBLIOTECA ROMANICA HISPANICA ;, 1982)
TRADUCCION DE: FERDINAND DE SAUSSURE. ORIGIN AND DEVELOPMENT OF HIS LINGUISTIC THOUGHT IN WESTERN STUDIES OF LANGUAGE. A CONTRIBUTION TO THE HISTORY AND THEORY OF LINGUISTICS